PERAN GURU DALAM MENANAMKAN KARAKTER DISIPLIN SISWA DI SMAN 1 TONGAS PROBOLINGGO: The Role of Teachers in Fostering Discipline among Students at SMAN 1 Tongas Probolinggo - Sinta Ma'sumah; Khoridatul Husnia; Lailatul Izzah; Lailatun Ni'mah; Istifaur Rosidah; Khoiriyah (STAI Ma'had Aly Al-Hikam Malang, 2026)
This article aims to examine the role of teachers, particularly teachers of Islamic Religious Education (PAI), Guidance and Counseling (BK) and student affairs, in instilling discipline in students at State Senior High School (SMAN) 1 Tongas, Probolinggo Regency. This article employs a qualitative and descriptive approach. Data were collected through observation, interviews, and documentation. Data analysis utilized the Miles and Huberman interactive model. The research findings indicate that all teachers at SMAN 1 Tongas serve as role models in fostering students’ disciplined character. PAI teachers play a role in internalizing student discipline through classroom and extracurricular learning. BK teachers play a role in helping students understand positive discipline rules and providing support when violations occur. In addition to the teachers’ roles, the instillation of student discipline is carried out through verbal and written media such as posters, as well as through the school’s positive culture. Artikel ini bertujuan menelaah peran guru, khusus Guru Pendidikan Agama Islam (PAI) serta Guru Bimbingan dan Konseling (BK) dan Kesiswaan dalam menanamkan karakter disiplin siswa di Sekolah Menengah Atas Negeri (SMAN) 1 Tongas Kabupaten Probolinggo. Artikel ini menggunakan pendekatan kualitatif dan jenis deskriptif. Data dikumpulkan melalui teknik observasi, wawancara dan dokumentasi. Analisis data menggunakan model interaktif Miles dan Huberman. Hasil penelitian menunjukkan bahwa semua guru di SMAN 1 Tongas berperan sebagai teladan dalam penanaman karakter disiplin siswa. Guru PAI berperan menginternalisasikan disiplin siswa melalui pembelajaran di kelas dan di luar kelas. Guru BK dan Kesiswaan berperan membantu siswa memahami aturan disiplin positif dan mendampingi ketika terjadi pelanggaran. Selain peran guru, penanaman karakter disiplin siswa melalui media lisan dan tulisan seperti poster, serta melalui budaya positif sekolah. Kata Kunci : Disiplin Siswa; Pendidikan Karakter; Peran Guru.